Nysius cymoides (Hemiptera: Lygaeidae), a potential emerging pest: overview of the information available to implement integrated pest management. Issue 1 (2nd January 2021) - Scaccini, Davide; Furlan, Lorenzo
Abstract: The present article reviews the literature on the biology, pest status and management of Nysius cymoides (Spinola) (Hemiptera: Lygaeidae), an agricultural pest that causes damage to multiple crop species in the Middle East and in Europe, where it may become an emerging pest. The polyphagy of the species and its capability to give rise to outbreaks, mainly during warm and dry periods, make the insect a major pest in a number of countries, as are other species of the same genus. Following our overview of the known aspects, Integrated Pest Management options are discussed in practical terms, with biological features and pest management of other Nysius species also being considered. In order to prevent pest infestations, an integrated framework approach also needs to consider agronomic practices such as weed cover and soil management. Future research would benefit from an assessment of proper methodologies for monitoring N. cymoides and the establishment of economic thresholds for susceptible crops and life stages based on practical parameters.